2011
DOI: 10.1177/0165551511408846
|View full text |Cite
|
Sign up to set email alerts
|

Scientific communication in Libya in the digital age

Abstract: This study seeks to understand the scientific communication activities of Libyan scientists, and their engagement with scientific publishing. The research embraces both formal and informal communication, and explores that behaviour in the context of a developing country, Libya. A mixed methods approach including desk research, a bibliometric study of recent scientific output, interviews with key informants, and a questionnaire survey with scientists is used to gather rich data and to generate deep insights int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…The finding of the study is consistent with the global trend reported by scholars (Costa & Meadows, 2000;Heterick, 2002;Jankowska, 2004;Mahajan, 2006;Mahmood et al, 2011;Vakkari, 2008) that electronic resources have a perceived positive effect on research productivity at universities around the world. In the Nigerian context, the finding of the study affirms recent research findings by Ajala et al (2010), Nwezeh (2010, and Popoola (2008) but contradicts results of some studies that were conducted in the early 2000s (Ehikhamenor, 2003a(Ehikhamenor, , 2003bJimba & Atinmo, 2000).…”
Section: Testing Of Hypothesessupporting
confidence: 90%
See 2 more Smart Citations
“…The finding of the study is consistent with the global trend reported by scholars (Costa & Meadows, 2000;Heterick, 2002;Jankowska, 2004;Mahajan, 2006;Mahmood et al, 2011;Vakkari, 2008) that electronic resources have a perceived positive effect on research productivity at universities around the world. In the Nigerian context, the finding of the study affirms recent research findings by Ajala et al (2010), Nwezeh (2010, and Popoola (2008) but contradicts results of some studies that were conducted in the early 2000s (Ehikhamenor, 2003a(Ehikhamenor, , 2003bJimba & Atinmo, 2000).…”
Section: Testing Of Hypothesessupporting
confidence: 90%
“…With a possible perceived positive effect of electronic information resources on the research process in developed countries (Brittain, 1989;Heterick, 2002;Jankowska, 2004;Mahmood, Hartley, & Rowley, 2011;Meadows, 1989;Vakkari, 2008) and a few contradicting research findings in Nigeria, Africa (Ehikhamenor, 2003a(Ehikhamenor, , 2003bJimba & Atinmo, 2000), Duque et al (2010) raised the poser of whether the "process of knowledge production is similar in the developed and developing worlds" (p. 4). In other words, if it is substantiated that there is a perceived positive effect due to accessibility and use of electronic resources on research productivity in developed countries, would the situation be the same in Nigerian universities?…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Kraut, Fish, Root & Chalfonte () emphasized that informal communication appears to be a dominant activity in organizations. Mahmood, Hatley & Rowley () described the informal communication activities between scientists, in which they interact directly through, for example, face‐to‐face discussion, telephone, fax, post, electronic mail, personal websites, and conferences.…”
Section: Introductionmentioning
confidence: 99%